Constructing electrospun 3D liquid metal adhesion channel on stretchable yarns for broad-range strain-insensitivity smart textiles - Yikun Duan; Zhaoyang Sun; Qiangqiang Zhang; Yalin Dong; Yagai Lin; Dongxiao Ji; Xiaohong Qin (Nature Communications)
Abstract Conductive fibers are crucial for smart textiles and wearable electronics, yet achieving satisfactory elasticity is challenging due to the mismatch between the substrate and the conductive material. Herein, we propose an adhesion channeling strategy that enables three-dimensional control of liquid metal (LM) flow on the yarn surface, allowing for the simultaneous deformation of both the LM and the yarn. This approach ensures that the yarns maintain a low resistance of 0.082 Ω/cm and exhibit conductivity stability across a wide strain range, with a resistance change (ΔR/R0) of only 0.703 at 600% strain. The yarn exhibits electrical stability under various mechanical stresses-including twisting, bending, pressing, and large-strain tensile cycling-as well as during washing processes. By modifying the functional materials within the electrospun fibers, we demonstrate the application of the yarns’ superior Joule heating effect for intelligent color regulation of fabrics, providing a feasible solution for the advanced design of smart textiles.